Design and performance evaluation of a pilot-scale pulsed vacuum infrared drying (PVID) system for drying of berries. Issue 10 (1st July 2020) - Zhang, Wei-Peng; Chen, Chang; Pan, Zhongli; Xiao, Hong-Wei; Xie, Long; Gao, Zhen-Jiang; Zheng, Zhi-An
Abstract: The objective of current work was to develop a new pilot-scale pulsed vacuum infrared drying (PVID) system for the drying of berries. The system design and drying performance evaluation for grape and goji berries are reported here. The PVID system consisted of three major sections, including infrared heating section, vacuum section, and a controlling section. Electrical infrared (IR) emitter was made with carbon fiber sheet at the thickness of 2–4 mm, which emitted IR wavelength of 1–30 μm. The control system was used to achieve paused pressure by switching the drying chamber pressure between atmospheric pressure (101 kPa) and vacuum (3–10 kPa) successively and maintaining the pressure for different time periods. Grapes and goji berries were dried in a single layer at three different temperatures (55, 65, and 75 °C) with an atmospheric duration ranging from 1 to 12 min and vacuum duration from 10 min to constant vacuum. The drying characteristic and quality of PVID dried berries were investigated and compared with that of hot air (HA) dried berries. Results showed that the IR heating temperature, atmospheric duration, and vacuum duration had significant effects ( p < .05) on the drying time. The optimum drying conditions for grapes and goji berries were IR heating at 65 °C, vacuum duration of 15 min, and atmospheric duration of 4 and 2 min, respectively. The corresponding drying time is nearly 720 min for grapes, and 450 min for goji berries. The PVID dried grapes and goji berries had more attractive color than that of HA dried ones. These findings demonstrated that PVID should be a promising method to produce high-quality dried berries. This study laid a good foundation for scaling up the technology in the future.